Análise do processo de ensino e aprendizagem de alunos em classes multisseriadas da escola Santa Rita em Igarapé – Miri – Pará - CORRÊA, Neidineia Oliva (2019)
The present work makes an analysis of the teaching and learning process in multisseriateclass, specifically in Santa Rita School, in Igarapé-Miri, with the objective from investigate what difficulties faced in the process of teaching and learning in the classes of the 3rd and 4th year of elementary school. The research was made by a case study in the teaching institution Santa Rita Municipal School, through from interviews with teachers and family of students with learning difficulties and through a script with key questions, in order to verify the reality experienced by the teacher and per students of school in the field, as well a achievements and challenges that are imposed on a daily basis. And, based on this local reality, as well as on teaching experience, is that this work is intended to demonstrate that the multisseriate classes of field education has a long way to go and challenges to be overcome, making it necessary a greater reflection on how to design a basic education of the field geared to the interests and socio-cultural development and economical of people who inhabit and working on the countryside, considering to their diferences historical and cultural so that they can to live with dignity, enjoying the rights due to them.